2021
DOI: 10.1016/j.isci.2021.102109
|View full text |Cite
|
Sign up to set email alerts
|

Coproduction of hydrogen and lactic acid from glucose photocatalysis on band-engineered Zn1-xCdxS homojunction

Abstract: Summary Photocatalytic transformation of biomass into value-added chemicals coupled with co-production of hydrogen provides an explicit route to trap sunlight into the chemical bonds. Here, we demonstrate a rational design of Zn 1-x Cd x S solid solution homojunction photocatalyst with a pseudo-periodic cubic zinc blende (ZB) and hexagonal wurtzite (WZ) structure for efficient glucose conversion to simultaneously produce hydrogen and lactic acid. The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 52 publications
0
58
0
Order By: Relevance
“…As can be seen in Figure 9, the heterojunction of BiOBr/Zn@SnO 2 with a suitable bandgap is activated under visible light irradiation, and the photogenerated electrons generated in the conduction band reduce the absorbed oxygen to form superoxide radicals. Furthermore, the produced superoxide radicals can be continuously transformed into other reactive substances under light irradiation, such as hydroxyl radicals, which promote the conversion of fructose to lactic acid [11]. The formation of lactic acid from fructose under alkaline conditions in the photorefinery start from the ring-opening of fructose, followed by hydrolysis (transaldol) of fructose in the presence of reactive oxygen species to produce glyceraldehyde and 1,3-dihydroxyacetone.…”
Section: Possible Pathways For Lactic Acid-lactate Production By Fruc...mentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen in Figure 9, the heterojunction of BiOBr/Zn@SnO 2 with a suitable bandgap is activated under visible light irradiation, and the photogenerated electrons generated in the conduction band reduce the absorbed oxygen to form superoxide radicals. Furthermore, the produced superoxide radicals can be continuously transformed into other reactive substances under light irradiation, such as hydroxyl radicals, which promote the conversion of fructose to lactic acid [11]. The formation of lactic acid from fructose under alkaline conditions in the photorefinery start from the ring-opening of fructose, followed by hydrolysis (transaldol) of fructose in the presence of reactive oxygen species to produce glyceraldehyde and 1,3-dihydroxyacetone.…”
Section: Possible Pathways For Lactic Acid-lactate Production By Fruc...mentioning
confidence: 99%
“…Duan et al [9] proposed coupling heterojunctions formed by two different semiconductor materials to modify charge transfer, and Chaves et al [10] suggested that bandgap engineering should be combined with homojunction as a means to modulate the redox potential and thus achieve efficient selection for sugar oxidation. Zhao et al [11] chose Zn 1-x Cd x S to perform a series of experiments on the modulation of bandgap and redox potential. They found that the reduction in bandgap and the increase in redox potential could, to some extent, reduce the hydrogen precipitation reaction of sugars while increasing the oxidation reaction and improving the selectivity of lactic acid, but all of their studies suffer from low lactate yields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, typical heterogeneous photocatalysts for carbohydrates reforming are composite materials on the basis of wide-gap semiconductor oxides (predominantly, TiO 2 [ 7 , 8 , 9 , 10 , 11 ] as well as perovskites LaFeO 3 [ 12 , 13 ]), sulfides (Zn 1−x Cd x S [ 14 ], CdS/MoS 2 [ 15 , 16 ]), tungstates (BiWO 6 [ 17 ]), and metal-free compounds (g-C 3 N 4 [ 18 , 19 , 20 ]). They were tested in relation to light-driven hydrogen production from glucose [ 21 ], xylose [ 22 ], fructose [ 23 ], sucrose [ 24 ], cellulose [ 25 , 26 ], and lignocellulose [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose photoreforming has rapidly developed through the application of novel photocatalysts . For example, Zhao et al employed a band-engineered zinc–cadmium photocatalyst for lactic acid (LA) and hydrogen production . Bai et al produced gluconic and glucaric acid from a modified carbon nitride by introducing nitrogen defects .…”
Section: Introductionmentioning
confidence: 99%